Growth of Bacillus spp. Isolated From Nipah Worm Intestine (Namalycastis rhodochorde) With Different Combination of pH and Salinity - Rikhsan Kurniatuhadi; Ari Hepi Yanti; Tri Rima Setyawati; Eka Karunia (Bioma : Jurnal Ilmiah Biologi, 2023)
Bacillus spp. (NrLtF1, NrLtF5, and NrLtG2) isolated from the digestive tract of the Nypa palm worm (Namalycastis rhodochorde) were assumed to have growth characteristics according to the habitat conditions of the nypa worm. Nypa worms live in estuary environments that are affected by seawater intrusion. Salinity and pH are two environmental factors affecting gastrointestinal isolates' growth from nypa palm worms. This study aimed to determine the effect of pH and salinity on the media on growth patterns and determine the optimum combination of pH and salinity for Bacillus spp. The study was conducted using a spectrophotometry method using a microplate reader with Glucose Yeast Peptone (GYP) as a medium for bacterial growth. The medium's pH and salinity values were adjusted by adding 5M NaOH and 5M HCl to obtain pH values of 4, 5, 6, and 7, respectively. Addition of NaCl to the growing medium to get salinity values of 5%, 10%, and 15%. Optimization was determined by incubation at a density of 595 nm at a temperature of 31oC for 24 hours. The results showed that Bacillus spp. could grow well at pH 6 with a salinity value of 15%, pH 6 with a salinity value of 10%, and pH 6 with a salinity value of 5% based on contour plot design. The Optimum growth of Bacillus spp. with pH and salinity expects to be a reference for developing feed products based on indigenous nypa palm worms.